2016
DOI: 10.1021/acssuschemeng.6b00525
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Mode Antifouling Ability of Thiol–Ene Amphiphilic Conetworks: Minimally Adhesive Coatings via the Surface Zwitterionization

Abstract: A series of antibiofouling amphiphilic conetwork (APCN) coatings combined with zwitterionic features are engineered by surface zwitterionization of spontaneously segregated poly­(N,N-dimethylaminoethyl methacrylate) (PDMAEMA) segments, where this dual-mode surface integration of both passive and active modes improves the entire antifouling efficiency against the adsorption of proteins and a widespread marine fouling organism (Phaeodactylum tricornutum). A clear difference in surface morphology and topography b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 65 publications
(84 reference statements)
0
29
0
Order By: Relevance
“…A new emerging trend should aim at integrating multiple functionalities in one amphiphilic polymer platform that are each tailored to operate via a specific mechanism and to accomplish a particular task to impact in a synergistic dual‐mode, i.e. active and passive, action on the secreted bioadhesive and the sensing size range of the colonising organisms . Definitely, a more thorough knowledge of the necessary requirements to comprehend and control the intertwined surface features of amphiphilic polymers will aid the development of future guiding principles and design rules that can be used broadly for achieving breakthroughs in marine antibiofouling application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A new emerging trend should aim at integrating multiple functionalities in one amphiphilic polymer platform that are each tailored to operate via a specific mechanism and to accomplish a particular task to impact in a synergistic dual‐mode, i.e. active and passive, action on the secreted bioadhesive and the sensing size range of the colonising organisms . Definitely, a more thorough knowledge of the necessary requirements to comprehend and control the intertwined surface features of amphiphilic polymers will aid the development of future guiding principles and design rules that can be used broadly for achieving breakthroughs in marine antibiofouling application.…”
Section: Discussionmentioning
confidence: 99%
“…active and passive, action on the secreted bioadhesive and the sensing size range of the colonising organisms. [166] Definitely, a more thorough knowledge of the necessary requirements to comprehend and control the intertwined surface features of amphiphilic polymers will aid the development of future guiding principles and design rules that can be used broadly for achieving breakthroughs in marine antibiofouling application. This will also help in solving global environmental problems caused by older chemical technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Super‐amphiphilic (the contact angles for water and oil both approach 0°) materials have aroused great interest during the past few decades [ 9 ] due to their importance in practical applications, and they can act as reusable heterogeneous catalytic system scaffolds, [ 10 ] perfect absorbent for emulsified wastewater, [ 11 ] antifogging and self‐cleaning oxide films, [ 12 ] and sensitizers in dye‐sensitized solar cells. [ 13 ] Silicone sponge possesses 3D porous organic network structure, which are nontoxic, highly flexible, stable, insulated, and chemically inert, [ 14–19 ] and many silicone sponges with excellent performance have been developed by various techniques in recent years.…”
Section: Methodsmentioning
confidence: 99%
“…1f that two peaks were added (-COO, 286.68 eV and C-N, 282.92 eV), which indicated that the reaction of thiol with a double bond was successful, and that of isocyanate and polyol was successful. 31,32 3.2 Thermogravimetric analysis (TGA)…”
Section: Characterizationmentioning
confidence: 99%